Digital Appearance in Shakespeare’s The Tempest - Baral, Rohit Raj (Kanya Journal, 2024)
This paper aims to make an analysis of the use of information and communication technology(ICT)y and the connection of its knowledge in the modern education system. It deals with the popularity of the English language and digital literacy among the students of language and literature and the use of technology in the modern education system. It has changed the whole scenario in English studies because everything is digitalized by modern science and technology. Digital literacy is required in the modern education system of language and literature teaching, learning, and writing. The article claims that this concept of technology and communication also was there in the Renaissance period of the 14th and 15th centuries in some forms which are available in Renaissance texts. The Tempest by William Shakespeare. Keith Green and Jill Lebihan’s concept of ‘Writing back’ is adopted to study classical literature to form new perspective and knowledge. The conclusion is made here that there was digital literacy and the concept of technology and communication in Renaissance times’ texts too as it is widely used in postmodern times.